Hands-on full stack web development with Aurelia develop modern and real-time web applications with Aurelia and Node.js - Argüelles Rojas, Diego Jose (Packt, 2018)
Isomorphic JavaScript has been a buzzword lately, allowing developers to utilize a single language throughout their web development stack and build cost-effective and scalable applications. This book is on one such modern web development stack which comprises of web technologies like MongoDB, Express.js, Aurelia.js, and Node
Keywords: Network analysis (Planning)